ACTIVITY OF BANKS IN THE CONDITIONS OF REGTECH FUNCTIONING - Zaporozhets, Svitlana (Socio-economic relations in the digital society, 2020)
The necessity of introduction and dissemination of the practice of RegTech functioning in Ukraine is investigated; the role of technological developments and digital transformation of the financial services market is substantiated. The essence of the concept of RegTech is described from the point of view of the Basel Committee on Banking Supervision. The main components of the subject area of application of RegTech are identified, along with already started projects. The author’s vision of the main prerequisites for the introduction and dissemination of the practice of RegTeh in Ukraine is presented. The group of subjects-recipients of effects from technological results of activity of the companies in the field of RegTech is generalized; the basic advantages of its introduction for banks are resulted. The modern tendencies of initiating the process of introduction of RegTeh practice in Ukraine at the initiative of the domestic regulator are investigated. The directions of innovative initiation of RegTeh in the activity of banks in accordance with the provisions of the developed strategy of Fin Tech development in Ukraine are substantiated. The main regulatory measures of the regulator aimed at the use of RegTeh tools are clarified. The consequences of the introduction of the regulatory «sandbox» are substantiated, among which: acceleration of market entry of new innovative solutions; dissemination of the use of innovative technologies in supervisory and regulatory processes; entry of the regulator into the global «sandbox». A number of indicators of successful implementation of the strategy for the development of RegTech are summarized: monitoring of financial innovations; timely updating of regulatory acts and policies; strengthening collection, analysis and regulatory oversight in the context of anti-money laundering; introduction of open bank standards and distributed registry technology; strengthening big data management and analytics; introduction of a framework for sustainable cyber security; promoting the formation of sustainable business models of financial institutions; improving financial literacy and protecting the rights of consumers of digital financial services. The directions of influence of RegTech functioning on the regulator of loading of domestic banks are characterized. The main preliminary transitions of RegTech implementation are presented and the necessity of application of the coordinated approach which consists in evolution of development of both Fin Tech, and RegTech representing early stages of deep change of parameters from the KYC approach to the KYD approach is provided.